Estimating abundance of an elusive cetacean in a complex environment: Harbor porpoises (Phocoena phocoena) in inland waters of Southeast Alaska - Zerbini, Alexandre N.; Goetz, Kimberly T.; Forney, Karin A.; Boyd, Charlotte (Frontiers in Marine Science, 2022)
The harbor porpoise (Phocoena phocoena) is common in temperate waters of the eastern North Pacific Ocean, including Southeast Alaska inland waters, a complex environment comprised of open waterways, narrow channels, and inlets. Two demographically independent populations are currently recognized in this region. Bycatch of porpoises in the salmon drift gillnet fisheries is suspected to occur regularly. In this study, we apply distance sampling to estimate abundance of harbor porpoise during ship surveys carried out in the summer of 2019. A stratified survey design was implemented to sample different harbor porpoise habitats. Survey tracklines were allocated following a randomized survey design with uniform coverage probability. Density and abundance for the northern and southern Southeast Alaska inland water populations were computed using a combination of design-based line- and strip-transect methods. A total of 2,893 km was surveyed in sea state conditions ranging from Beaufort 0 to 3 and 194 harbor porpoise groups (301 individuals) were detected. Sighting data from surveys conducted between 1991 and 2012 were used to calculate the probability of missing porpoise groups on the survey trackline (g[0]=0.53, CV=0.11). Abundance of the northern and southern populations were estimated at 1,619 (CV=0.26) and 890 (CV=0.37) porpoises, respectively. Bycatch estimates, which were only obtained for a portion of the drift gillnet fishery, suggest that mortality within the range of the southern population may be unsustainable. Harbor porpoises are highly vulnerable to mortality in gillnets, therefore monitoring abundance and bycatch is important for evaluating the potential impact of fisheries on this species in Southeast Alaska.